التجربة الدينية من وجهة نظر الفلسفة البراغماتية - عبد الحسين, قاسم صاحب (Al-Adab Journal, 2019)
The Religions experience according to the pragmatic philosophy. These researches show the raglan experience in three philosophers, pierce, James, Dewey. And also deal with the pragwutic philosophy and his up from evectional with aphis subject. It this faith of the men in goa.